Financial & managerial accounting the basis for business decisions - Williams, Jan R.; Bettner, Mark S.; Carcello, Joseph V. (McGraw-Hill Education, 2021)
"As our eyes are drawn upward to the skyline of great cities, it's important to remember that these impressive constructions are able to reach such heights only because their foundations are strong. In much the same way, being successful in the business world begins with fundamental courses like financial and managerial accounting. It is only when students have a firm grasp of concepts like the accounting cycle and managerial decision making that they have a base on which to stand, a strong foundation on which to grow. In this edition, as before, the Williams team has revised the text with a keen eye toward the principle of helping students establish the foundation they will need for future success in business. However, through new coverage of International Financial Reporting Standards and a revised globalization chapter, the Williams book also introduces students to larger themes and evolving concerns. This dual emphasis allows students to keep their eyes trained upward even as they become solidly grounded in accounting fundamentals"--Provided by publisher.